106 Epidermoid Metaplasia of the Esophagus. (11th January 2018) - Talwar, Aditya; Mohanty, Alok; Yuan, Justin; Kulkarni, Abhijit; Silverman, Jan; Liu, Yulin; Miller, Stacey
Abstract: Esophageal epidermoid metaplasia is rare lesion of the esophagus, associated with alcohol and tobacco abuse. This condition affects middle-aged to elderly patients with a slight female predominance (1:1.8). Signs and symptoms typically include dysphagia and gastroesophageal reflux disease. The metaplastic changes are usually seen in the middle to distal esophagus. We report a case of a 53-year-old woman with a history of dysphagia and food impaction for approximately one year. An upper endoscopy performed at that time identified a food bolus, which was removed, and a small esophageal stricture, which was dilated by scope passage. A follow-up endoscopy one year later at an outside facility showed diffuse mucosal changes characterized by scarring, whitish, metaplastic-appearing mucosa, most significant in the mid esophagus. The biopsies of these changes demonstrated epithelial hyperplasia, surface orthokeratosis, and prominent hypergranulosis, features consistent with epidermoid metaplasia. A subsequent biopsy performed approximately one year later at our institution showed the same histologic features. No squamous dysplasia was noted. Epidermoid metaplasia, which is analogous to oral leukoplakia, is histologically characterized by epithelial hyperplasia, a thickened basal layer, acanthotic midzone, a prominent granular cell layer, and superficial hyperorthokeratosis. Adjacent high-grade squamous cells dysplasia or squamous cell carcinoma can be seen in some patients, and the risk factors of developing epidermoid metaplasia are similar to those of oral leukoplakia. Therefore, epidermoid metaplasia can be considered a preneoplastic condition and may lead to dysplasia or carcinoma. As a result, a diagnosis of epidermoid metaplasia warrants close clinical and endoscopic follow up, in which there are no clearly defined guidelines.